Oxalate Oxidase for In Situ H2O2‐Generation in Unspecific Peroxygenase‐Catalysed Drug Oxyfunctionalisations. (25th August 2022) - Romero, Elvira; Johansson, Magnus J.; Cartwright, Jared; Grogan, Gideon; Hayes, Martin A.
Abstract: H2 O2 ‐driven enzymes are of great interest for industrial biotransformations. Herein, we show for the first time that oxalate oxidase (OXO) is an efficient in situ source of H2 O2 for one of these biocatalysts, which is known as unspecific peroxygenase (UPO). OXO is reasonably robust, produces only CO2 as a by‐product and uses oxalate as a cheap sacrificial electron donor. UPO has significant potential as an industrial catalyst for selective C−H oxyfunctionalisations, as we confirm herein by testing a diverse drug panel using miniaturised high‐throughput assays and mass spectrometry. 33 out of 64 drugs were converted in 5 μL‐scale reactions by the UPO with OXO (conversion >70 % for 11 drugs). Furthermore, oxidation of the drug tolmetin was achieved on a 50 mg scale (TONUPO 25 664) with 84 % yield, which was further improved via enzyme immobilization. This one‐pot approach ensures adequate H2 O2 levels, enabling rapid access to industrially relevant molecules that are difficult to obtain by other routes. Abstract : High‐throughput μL‐scale screenings revealed optimal conditions for in situ H2 O2 ‐generation using oxalate oxidase in bioconversions catalysed by unspecific peroxygenase. This enzymatic tandem exhibits extraordinary potential for selective C−H oxyfunctionalisation reactions of complex drug scaffolds.